Reverse Phase Protein Arrays for Compound Profiling. Issue 3 (13th September 2016) - Moerke, Nathan; Fallahi‐Sichani, Mohammad
Abstract: Reverse phase protein arrays (RPPAs), also called reverse phase lysate arrays (RPLAs), involve immobilizing cell or tissue lysates, in small spots, onto solid supports which are then probed with primary antibodies specific for proteins or post‐translational modifications of interest. RPPA assays are well suited for large‐scale, high‐throughput measurement of protein and PTM levels in cells and tissues. RPPAs are affordable and highly multiplexable, as a large number of arrays can readily be produced in parallel and then probed separately with distinct primary antibodies. This article describes a procedure for treating cells and preparing cell lysates, as well as a procedure for generating RPPAs using these lysates. A method for probing, imaging, and analyzing RPPAs is also described. These procedures are readily adaptable to a wide range of studies of cell signaling in response to drugs and other perturbations. © 2016 by John Wiley & Sons, Inc.